Multiple output high current power supply - Nill, Jim Ruther (2006)
Mobile Robotics Laboratory or MOBOT uses motors with a rating of 12V for their undergraduate laboratory projects. The multiple-output, high current power supply was designed to be used in the said laboratory of the EEE Department. Outputs are available in 5V at 1A, 12V at 1A, and 12V at 15A output was chosen to provide the rated voltage to the motors available in the MOBOT laboratory. The other outputs chosen to match the standard power supply used by computers. Two DC-DC converter topologies will be used to attain the specifications of the project. To control the switching of the converters, pulse width modulation control will be used. Alongside this, current mode control will be implemented. A battery will be used as power source to allow better mobility.